Silencing of SlPL, which encodes a pectate lyase in tomato, confers enhanced fruit firmness, prolonged shelf‐life and reduced susceptibility to grey mould. Issue 12 (16th May 2017) - Yang, Lu; Huang, Wei; Xiong, Fangjie; Xian, Zhiqiang; Su, Deding; Ren, Maozhi; Li, Zhengguo
Summary: Pectate lyase genes have been documented as excellent candidates for improvement of fruit firmness. However, implementation of pectate lyase in regulating fruit postharvest deterioration has not been fully explored. In this report, 22 individual pectate lyase genes in tomato were identified, and one pectate lyase gene SlPL (Solyc03g111690) showed dominant expression during fruit maturation. RNA interference of SlPL resulted in enhanced fruit firmness and changes in pericarp cells. More importantly, the SlPL ‐RNAi fruit demonstrated greater antirotting and pathogen‐resisting ability. Compared to wild‐type, SlPL ‐RNAi fruit had higher levels of cellulose and hemicellulose, whereas the level of water‐soluble pectin was lower. Consistent with this, the activities of peroxidase, superoxide dismutase and catalase were higher in SlPL ‐RNAi fruit, and the malondialdehyde concentration was lower. RNA‐Seq results showed large amounts of differentially expressed genes involved in hormone signalling, cell wall modification, oxidative stress and pathogen resistance. Collectively, these data demonstrate that pectate lyase plays an important role in both fruit softening and pathogen resistance. This may advance knowledge of postharvest fruit preservation in tomato and other fleshy fruit.